Evaluation of hydrotropic pretreatment on lignocellulosic biomass. (August 2016) - Devendra, Leena P.; Kiran Kumar, M.; Pandey, Ashok
Highlights: Hydrotropic pretreatment leads to reduction in surface coverage by lignin. XPS and TOF-SIMS analysis provide important insights on surface chemical studies. Hydrotropic lignin can have potential application as bio based polymer. Enzymatic yield of glucose was enhanced by hydrotropic pretreatment. Abstract: The production of cellulosic ethanol from biomass is considered as a promising alternative to fossil fuels, providing a sustainable option for fuels production in an environmentally compatible manner. The presence of lignin poses a significant challenge for obtaining biofuels and bioproducts from biomass. Part of that problem involves understanding fundamental aspects of lignin structure which can provide a pathway for the development of improved technologies for biomass conversion. Hydrotropic pretreatment has several attractive features that make it an attractive alternative for biofuel production. This review highlights the recent developments on hydrotropic pretreatment processes for lignocellulosic biomass on a molecular structure basis for recalcitrance, with emphasis on lignin concerning chemical structure, transformation and recalcitrance. The review also evaluates the hydrotropic delignification in comparison to alkaline delignification on lignin reduction and surface coverage by lignin. The effect of hydrotrope pretreatment on enzymatic saccharification has also been discussed.